2020
DOI: 10.1088/1361-6501/ab79c8
|View full text |Cite
|
Sign up to set email alerts
|

Automatic crack recognition for concrete bridges using a fully convolutional neural network and naive Bayes data fusion based on a visual detection system

Abstract: Regular inspections of bridge substructures are very important for evaluating bridge health, since early detection and assessment offer the best chances of bridge repair. However, the traditional inspection methods of checking defects with visual features cannot meet engineering needs sufficiently. Although deep-learning methods have recently demonstrated a remarkable improvement in image classification and recognition, there are still difficulties, such as the countless parameters and large model training set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Image processing is accompanied by filtering of the image and detection of defective areas. To make this type of algorithm work, a separate database of damage profiles must be created to compare damage profiles throughout processing, which must be done for different conditions [22].…”
Section: Resultsmentioning
confidence: 99%
“…Image processing is accompanied by filtering of the image and detection of defective areas. To make this type of algorithm work, a separate database of damage profiles must be created to compare damage profiles throughout processing, which must be done for different conditions [22].…”
Section: Resultsmentioning
confidence: 99%
“…Research in many other fields can be found too; in [36], for predicting water floods, or in [23], for earthquake predictions. Another interesting study is presented in [18], where they propose an automatic bridge crack recognition tool based on CNN and NB.…”
Section: Related Workmentioning
confidence: 99%
“…ey further adopted the segmentation network of FCN and Naïve Bayes data fusion (NB-FCN) to realize the location of concrete cracks. e cracks were quantified by introducing postprocessing with accuracy being 93.2% [20].…”
Section: Introductionmentioning
confidence: 99%